PENGARUH BAURAN KOMUNIKASI PEMASARAN TERHADAP CITRA MERK MINYAK GORENG SANIA PADA PT. SARI AGROTAMA PERSADA - Agung Rachmadi; Susi Indriyani; Hasbullah Hasbullah (Universitas Bandar Lampung (UBL), 2021)
The relatively low share of the Sania Cooking Oil Brand shows the lack of public desire to use this cooking oil, so that efforts are needed to communicate the strengths and advantages of the brand. The purpose of this study was to determine and analyze the effect of advertising, sales promotion, personal selling, direct marketing and public relations together on the brand image of Sania cooking oil at PT Sari Agrotama Persada. This study used qualitative and quantitative methods, and then the data in the study were obtained from the results of distributing questionnaires with a total sample of 104 customers. The analytical tool used is in the form of multiple linear regression analysis, t test and F test. Based on the results of the discussion, it can be concluded from the partial hypothesis test that advertising has a significant effect on brand image, sales promotion has a significant effect on brand image, personal selling has a significant effect on brand image, direct marketing has a significant effect on brand image and public relations has a significant effect on brand image. Simultaneous hypothesis testing that advertising, sales promotion, personal selling, direct marketing and public relations together have a significant effect on the brand image of PT Sari Agrotama Persada.